Reforming the fiscal rulebook for the euro area - and the challenge of old and new public debt - Jan Priewe (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2021)
Upholding the EU fiscal rules at the elevated public debt level due to the Corona crisis would trigger a phase of long-standing austerity in the euro area. In this study, major proposals for reforms are reviewed, with a critical focus on the expenditure rule, which is central in many think-tanks' and academic researchers' advice. A different reform based on a fiscal analogue to the well-known Taylor-rule for monetary policy is designed here. It is argued that under a low-interest environment growth rates exceed interest rates, a fact not compatible with the present ruleset and with far-reaching consequences. This requires redefining debt sustainability. The proposal chooses as the operational variable for fiscal policy primary balances rather than structural balances. The anchor for fiscal stability, until know the 60% cap on public debt, should be replaced by a cap on the interest payments on public debt at roughly 3% of GDP. This allows higher fiscal space for investment and innovations. The fact that the interest rate burden of all Member States in the euro area stands at the lowest level ever experienced, although the debt level is at an all-time high, clarifies that the focus on the debt ratio is misleading. Change could be possible in the secondary law of the EU without change of the Treaties.
Keywords: 330; Fiskalpolitik; Stabilitäts- und Wachstumspakt; Fiskalpakt; Schuldenbremse; Staatsschulden